(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Drug resistance is a frequent problem with chemotherapy-based cancer treatments. Secondary metabolites of plants with anticancer potential can be successfully enhanced at the nanoscale. Lycopene have a molecular formula C40H56. It is a tetraterpene and a carotene used in cosmetics as antiwrinkle agent, has the capacity to kill cancer cells by impeding cellular proliferation. Tamoxifen, a selective oestrogen receptor modulator, is employed to treat oestrogen receptor-positive breast cancer, reduce the risk of invasive breast cancer following surgery, or lessen the risk of breast cancer in high-risk women. To improve bioavailability and have a synergistic effect, Lycopene and TAM loaded dammar gum nanoparticles (LTDNPs) were made using oil in oil (O/O) emulsion solvent evaporation procedures. Zeta potential, a measure of a nanoparticles relative stability, was found to be -45.1 mV for LTDNPs. The percentage encapsulation efficiency values for Lycopene and TAM were found to be 70% and 76%, respectively. The LTDNPs have particles with a size between 28 and 32 nm, according to TEM. Compared to free Lycopene and TAM particles alone, the LTDNPs had far stronger anti-oxidant and anti-cancer capabilities and had sustained release. The in vitro experiments revealed that the combination of Lycopene, TAM, and dammar gum significantly inhibited the growth of MCF-7 cell lines compared to Lycopene, TAM, and dammar gum together, highlighting the combination’s substantial anticancer potential.